Structural transformations and physical properties of (1 − x) Na0.5Bi0.5TiO3 − x BaTiO3 solid solutions near a morphotropic phase boundary. (31st December 2018) - Mohanty, Hari Sankar; Dam, Tapabrata; Borkar, Hitesh; Pradhan, Dhiren K; Mishra, K K; Kumar, Ashok; Sahoo, Balaram; Kulriya, Pawan K; Cazorla, C; Scott, J F; Pradhan, Dillip K
Abstract: Piezoelectric and other physical properties are significantly enhanced at (or near) a morphotropic phase boundary (MPB) in ferroelectrics. MPB materials have attracted significant attention owing to both fundamental physics as well as the possibility of well-regulated energy and information storage devices which are dominated by lead (Pb)-based materials. Here, we report the crystal structure, Raman spectra, dielectric constant and polarization near the MPB of lead free (1 − x ) Na0.5 Bi0.5 TiO3 − x BaTiO3 (0.00 ⩽ x ⩽ 0.10) solid-solution, prepared by sol–gel auto combustion technique and sintered by microwave sintering technique. With the addition of BaTiO3 into Na0.5 Bi0.5 TiO3, it induces a structural phase transition from R 3 c (a single phase) to R 3 c + P 4 mm (a dual phase) close to x = 0.06 and 0.07 and transform to a high symmetry tetragonal phase P 4 mm at higher compositions ( x = 0.08 to 0.10) as evident from our x-ray Rietveld refinement and Raman spectroscopic results. We perform first-principles calculations based on density functional theory that confirm a structural transition from a rhombohedral to a tetragonal phase under increasing x . In the prepared solid solution, an anomalous enhancement of remnant polarization ( ) was observed for x = 0.06 and 0.07, which has been explained based on the existence of the MPB. On the other hand, the value of coercive field was found to be decreased linearly from x = 0.00 to 0.06; it is constant for higher compositions. Further details of the ferroelectric properties on the electric field poled samples have been studied and compared with the as-grown (unpoled) samples.